2004
DOI: 10.1515/znb-2004-0807
|View full text |Cite
|
Sign up to set email alerts
|

Ethenetetracarbonitrile and Heterocyclization of Symmetrical Dithiobiurea as well as Thioureidoethylthiourea Derivatives

Abstract: N,N’-Disubstituted hydrazinecarbothioamides 6a - c and substituted thioureidoethylthioureas 12a - c react with ethenetetracarbonitrile (TCNE) in ethyl acetate or chlorobenzene to form the derivatives of pyrazole 7, 8; thiadiazole 10, 11 thiadiazepine 9, thiadiazepane 13, imidazolidine 14 and diazepine 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Addition of two equivalents of ethenetetracarbonitrile 58 to a solution of 1,6‐disubstituted‐2,5‐dithiobiureas 4 in ethyl acetate at room temperature led to the formation of thiadiazole derivatives 50 and 53 as side products (Scheme ) [83].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of two equivalents of ethenetetracarbonitrile 58 to a solution of 1,6‐disubstituted‐2,5‐dithiobiureas 4 in ethyl acetate at room temperature led to the formation of thiadiazole derivatives 50 and 53 as side products (Scheme ) [83].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
“…Addition of two equivalents of ethenetetracarbonitrile 58 to 1,6‐disubstituted‐2,5‐dithiobiureas 4 in ethyl acetate lead to the formation of 7‐amino‐2‐substituted imino‐2 H ‐[1,3,4]thiadiazepine‐5,5,6‐tri‐carbonitriles 124 (Scheme ) [83].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
“…Irradiation of glyoxylic acid methylester thiosemicarbazones in methanol solution gave triazines [18]. On the other hand, the interaction of thiosemicarbazides with ethenetetracarbonitrile and benzo-as well as naphthoquinones as -acceptors afforded thiazole, thiazine, thiadiazole, thiadiazine, thiadiazepine, pyrazine and indazole derivatives [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclization of suitable open-chain organic molecules such as symmetrical N 1 ,N 2 -disubstituted hydrazine-1,2-carbothioamides (symmetrical 1,6-disubstituted 2,5-dithiobiureas, 1a-c) is a classical and very popular approach to the synthesis of N 2 ,N 5 -disubstituted 1,3,4-thiadiazole-2,5-diamines, 1-7 1,3,4-thiadiazole-2-thione, 5,7 and 1,2,4-triazole-3-thiol derivatives. 5 Reactions of 1,6-disubstituted 2,5-dithiobiureas with 2,3,5,6-tetrahalo-1,4-benzoquinones affords 4,1,2-benzothiadiazine-5,8-diones and tetrahalothiaanthrene-1,1,6,9-tetraones.…”
mentioning
confidence: 99%
“…6 Pyrazole, thiadiazole, and thiadiazepine derivatives are formed during the reaction of 1,6-disubstituted 2,5-dithiobiureas with ethenetetracarbonitrile. 7 It has been reported that when more than one product can be obtained at the same time in a particular reaction good to excellent selectivities can often be achieved by means of a suitable choice of the cyclizing agent and conditions. 8,9 There are indications that bis-heterocyclic compounds display much better antibacterial activity than the simple heterocyclic compounds.…”
mentioning
confidence: 99%